The effect of thermocyclic aging on color stability of high translucency monolithic lithium disilicate and zirconia ceramics luted with different resin cements: an in vitro study - Linah M. Ashy; Adnan Al-Mutairi; Tariq Al-Otaibi; Lulwa Al-Turki (BMC, 2021)
Abstract Background High-translucency monolithic zirconia were developed to combine the esthetics of all ceramic restorations with the strength properties of zirconia. The purpose of this study was to compare the color stability of high-translucency monolithic zirconia ceramics with lithium disilicate luted using light-cure versus dual-cure resin cements following thermocyclic aging. Methods Forty specimens, each composed of 10 × 10 × 1 mm ceramic slice luted to dentin surface of an extracted tooth, were prepared and assigned into four groups (n = 10) as follows; LiDi/LC: lithium disilicate luted by light-cure resin cement; LiDi/DC: lithium disilicate luted by dual-cure resin cement; Zr/LC: zirconia luted by light-cure resin cement; and Zr/DC: zirconia luted by dual-cure resin cement. Color analysis of the specimens was performed before and after 3000 thermal cycles by means of spectrophotometry. The CIE L*a*b* values of the specimens were measured, and data were analyzed statistically at a significance value of p < 0.05. Results Thermocycling resulted in a significant change in color coordinates of specimens with an overall ΔE = 3.59 ± 1.60, but there was no statistically significant difference in the color change value among all tested groups (P = 0.756). Conclusions At 1 mm restoration thickness, the color stability of high-translucency monolithic lithium disilicate and zirconia ceramics were not significantly different irrespective of the cement type used. Clinical implication Understanding the difference in color stability of dental ceramics may help in determining long-term esthetic result.